Utilización de la thiourea como agente alternativo para lixiviar minerales altamente refractarios en la recuperación de oro - Meza Carranza, Erix Heybilder (2012)
In the present work, the recovery of gold by the acid leaching method with constant stirring from a highly refractory ore from the metallurgical laboratory of the National University of Trujillo, Faculty of Metallurgical Engineering (Law 2.84 onz Au / TM); the independent variables were evaluated as the concentration of thiourea solution and agitation time. The granulometry of the refractory mineral was 100% solids and 200 mesh and the tests were carried out in the mineral processing laboratory of the metallurgical engineering department. In the experimental part, they were carried out for cylinder stirring tests for 72 hours of constant stirring and chemical composition of the refractory mineral, by means of dry-run analysis and atomic absorption, and the statistical analysis of the student test was performed for a single sample of data and has the most significant variables in the gold recovery for this research work, is the concentration of thiourea solution and stirring time. In addition, the best gold recovery result was obtained when 72 hours of optimum agitation was reached, reaching a recovery of gold up to 71.73% Au. It was shown that this method of acidic leaching with constant agitation in the presence of ferric sulphate is viable for processing highly refractory minerals